Design and performance evaluation of a healthcare distribution network towards maintaining a direct-to-customer policy. Issue 2 (3rd April 2017) - Hosseini, Ahmad; Johansson, Sara; Westberg, My
ABSTRACT: This work considers the multimodal distribution network of a healthcare company, where the stage of distributing to customers in a specific region is optimized. A time-evolving mixed-integer linear program is developed aimed at making tactical decisions; more specifically, to determine the best strategy for distributing the products from the manufacturing site (Mfg) to primary distribution centers (PDPs) and/or regional distribution centers (RDPs) and from them to customers. The company uses one Mfg and three different RDPs, and several PDPs. To account for variability in demand, the model is run under one-year actual data and the results are analyzed to obtain the best distribution scenario. The experiments show that the ratio of direct shipments can improve and demonstrate that cost reduction and modality improvement can be achieved within the network. An extensive sensitivity analysis is also conducted to show the effect of the model parameters on its performance.